Study of The Level of Compliance and Side Effects of Covid-19 Vaccination at Pakuan Baru Community Health Center - Nandita Almira Salsabila; Santi Perawati; Medi Andriani (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Covid-19 vaccination is one of the government programs to prevent Covid-19 transmission. Pakuan Baru Community Health Center has implemented the vaccination program, but its implementation has not been optimal. This is because people are still reluctant to carry out vaccinations, people are reluctant to vaccinate because they have poor knowledge about the covid-19 vaccine and have anxiety about the side effects caused after doing the covid-19 vaccine. This study aims to determine the level of compliance and side effects of Covid-19 vaccination at the Pakuan Baru Community Health Center in South Jambi. This research is a quantitative study with a descriptive approach. The research was conducted in July 2022. The population of this study were people aged > 17 years in Pakuan Baru Village in 2022 totaling 7,607 people. The research sample of people aged> 17 years in Pakuan Baru Village with a sample size of 118 people. The sampling technique used purposive sampling technique. Data collection methods by interview using a questionnaire. Data were analyzed descriptively. The results showed that out of 118 respondents, 60.17% of respondents complied with the covid-19 vaccine, 56.78% of respondents had good knowledge and 42.22% of respondents had poor knowledge. Local side effects felt by respondents were bone pain and swelling. Systemic side effects experienced by respondents were fever, headache and malaise. Based on the results of the study, it was concluded that most respondents had a good level of knowledge, most of them had good knowledge about the covid-19 vaccine. Side effects after doing the covid-19 vaccine are bone pain, swelling, fever, headache and malaise. It is hoped that the Pakuan Baru Public Health Center will hold counseling on the Covid-19 Vaccine so as to increase public knowledge about the importance of the covid-19 vaccine so that they want to do the covid-19 vaccine.Keywords: Covid-19 Vaccine, Compliance, Side Effects